Static and Dynamic Stability of a Multi-stepped Timoshenko Column Including Self-weight. (August 2018) - Uribe-Henao, A. Felipe; Zapata-Medina, David G.; Arboleda-Monsalve, Luis G.; Aristizabal-Ochoa, J. Dario
Abstract: A simplified and easy to implement approach for the solution of the static and dynamic stability of a Timoshenko column with multiple partitions is derived in a classic and condensed manner. The proposed methodology includes a non-uniformly distributed axial load along the structural member which can represent the self-weight of columns, chimneys, tall buildings or the axial load on piles induced by downdrag forces. The proposed model includes the effects of shear deformations along the member and the second-order shear force induced by the applied axial load as the member deforms. The effects of the self-weight on the structural member stability are studied using the proposed approach and conclusions regarding the contribution of the self-weight and discrepancies by neglecting it are presented. Three comprehensive examples including columns with weakened sections, distributed axial loads arising from the self-weight, symmetrical tapered sections, and stepped cross sectional members are included to validate and show the applicability of the proposed formulation.